2010
DOI: 10.1108/14777271011035031
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health care and patient satisfaction

Abstract: PurposeThe aim of this research is to examine the major factors affecting patients' perception of cumulative satisfaction and to address the question whether patients in Istanbul evaluate quality of health care to be similar or different to that of the Kazakhstani, Egyptian and Jordanian patients.Design/methodology/approachA conceptual model including behavioural dimensions of patient‐physician relationships and patient satisfaction has been used for approach. As the empirical research setting, this study conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…One study found that interaction of phone responding staff in health services was another important factor of patient satisfaction. 99 The physicians and nurses care were assessed by their affective behaviours: friendliness, sincerity, concerns, 55,87 sympathy, empathy, 45,49,58,90,94,97,106,130 kindness, courtesy to patients 23,40,87 and their family or friends, 97 and respect for patient preferences. 1,3,9,10,12,13,20,24,26,27,48,54,71,81,83,94,96,104,121,123,127,130 Peer reView Patients recommended doctors to others regarding their affective behaviours, 20 rather than their competency.…”
Section: Interpersonal Carementioning
confidence: 99%
See 1 more Smart Citation
“…One study found that interaction of phone responding staff in health services was another important factor of patient satisfaction. 99 The physicians and nurses care were assessed by their affective behaviours: friendliness, sincerity, concerns, 55,87 sympathy, empathy, 45,49,58,90,94,97,106,130 kindness, courtesy to patients 23,40,87 and their family or friends, 97 and respect for patient preferences. 1,3,9,10,12,13,20,24,26,27,48,54,71,81,83,94,96,104,121,123,127,130 Peer reView Patients recommended doctors to others regarding their affective behaviours, 20 rather than their competency.…”
Section: Interpersonal Carementioning
confidence: 99%
“…The physical environment aspects that predicted to be correlated to patient satisfaction were pleasantness of the atmosphere, room comfort, bedding, 23,83 cleanliness, 40,55,66,83,90,110,121,130 noise level, 57 temperature convenience, lighting convenience, food service, 23,40,83 bathroom comfort, 111 clarity of sign and directions, arrangement of equipment and facilities, and parking. 1,12,20,23,48,51,54,55,58,83,89,[96][97][98]106,118,130 in some studies, physical environment aspects were named as tangibles, which originated from SerVQUAL analysis by Parasuraman. 4,45,128 we found two studies demonstrated that more appealing hospital rooms potentially have had effects on patient evaluation 55 on most dimensions (health care personnel, food service, and housekeeping staff) of their hospital experience.…”
Section: Physical Environmentmentioning
confidence: 99%
“…It is interesting to note that all criteria in Table 7 (except for volunteering) figure among the most relevant patient satisfaction criteria present in Fig. 5: exams and treatment (or medical exams as in the chart; see, for example, De Salins et al., 2016); food quality (Bikker and Thompson, 2006; Camgöz‐Akdağ and Zineldin, 2010; Schoenfelder et al., 2011; Schaal et al., 2017); health staff, namely, the nursing care (e.g., Brown et al., 2005; Bergmann et al., 2020; Kinnear et al., 2020); obtained information (e.g., Messina et al., 2014; Meng et al., 2018; Davis‐Dao et al., 2020); accommodations (e.g., Ladhari and Rigaux‐Bricmont, 2013; Fatima et al., 2018; Prado‐Galbarro et al., 2020); and medical services, namely, the medical care and the discharge process (e.g., Mcfarland et al., 2015; Kamra et al., 2016; Kinnear et al., 2020). Therefore, we can conclude that despite the divergences of the three methods, our results are robust, meeting the main findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, much work remains to be done to improve their satisfaction with healthcare (Camgöz-Akdag and Zineldin 2010; Yasar 2011; Kacak et al 2014). …”
Section: Introductionmentioning
confidence: 99%